Association of prostate cancer polygenic risk score with number and laterality of tumor cores in active surveillance patients. Issue 10 (6th May 2021) - Xu, Jianfeng; Isaacs, William B.; Mamawala, Mufaddal; Shi, Zhuqing; Landis, Patricia; Petkewicz, Jacqueline; Wei, Jun; Wang, Chi‐Hsiung; Resurreccion, W. Kyle; Na, Rong; Bhanji, Yasin; Novakovic, Kristian; et al.
Abstract: Background: Prostate cancer (PCa) is characterized by its tendency to be multifocal. However, few studies have investigated the endogenous factors that explain the multifocal disease. The primary objective of the current study is to test whether inherited PCa risk is associated with multifocal tumors in PCa patients. Methods: Subjects in this study were PCa patients of European ancestry undergoing active surveillance at Johns Hopkins Hospital ( N  = 805) and NorthShore University HealthSystem ( N  = 432). The inherited risk was measured by genetic risk score (GRS), an odds ratio‐weighted and population‐standardized polygenic risk score based on known risk‐associated single nucleotide polymorphisms. PCa multifocality was indirectly measured by the number and laterality of positive tumor cores from a 12‐core systematic biopsy. Results: In the combined cohort, 35.7% and 66.3% of patients had ≥2 tumor cores at the initial diagnostic biopsy and on at least one subsequent surveillance biopsy, respectively. For tumor laterality, 7.8% and 47.8% of patients had bilateral tumor cores at diagnostic and surveillance biopsies, respectively. We found, for the first time, that patients with higher numbers of positive cores at diagnostic and surveillance biopsies, respectively, had significantly higher mean GRS values; p  = .01 and p  = 5.94E−04. Additionally, patients with bilateral tumors at diagnostic and surveillance biopsies, respectively, had significantly higher mean GRS values than those with unilateral tumors; p  = .04 and p  = .01. In contrast, no association was found between GRS and maximum core length of tumor or tumor grade at diagnostic/surveillance biopsies (all p  > .05). Finally, we observed a modest trend that patients with higher GRS quartiles had a higher risk for tumor upgrading on surveillance biopsies. The trend, however, was not statistically significant ( p  > .05). Conclusions: The associations of GRS with two measurements of PCa multifocality (core numbers and laterality) provide novel and consistent evidence for the link between inherited PCa risk and multifocal tumors.